Early initiation of breastfeeding and colostrum feeding among mothers of children aged less than 24 months in Debre Tabor, northwest Ethiopia: a cross-sectional study - Bereket Molla Abie (BMC Research Notes, 2019)
Abstract Objective To assess early initiation of breastfeeding and colostrum feeding practice among mothers of children aged less than 24 months in Debre Tabor. Result Two hundred ninety-seven (297) mothers of children aged less than 24 months participated which made the response rate of 98.1%. Among a total of 297 participants, early initiation of breastfeeding was practiced by 76.8% of mothers. Nearly three-fourths (74.4%) of mothers gave colostrum to their index child. The prevalence colostrums feeding and early initiation of breast feeding is low in Debre Tabor. Improving practice of initiation of breastfeeding and colostrums is recommended by counseling women regarding breastfeeding during ANC visit.